Social networking sites: Can midwives and nurses working with adolescent mothers harness their potential value?. Issue 3 (12th October 2020) - Nolan, Samantha J.; Hendricks, Joyce; Williamson, Moira; Ferguson, Sally L.
Abstract: Aim: This paper aims to discuss social networking sites as potentially salutogenic, culturally relevant extensions to maternity care provision for adolescent mothers. Background: Studies report that online networking may enhance social capital, a concept linked to enhanced well‐being, particularly for marginalized individuals. Improving outcomes for adolescent mothers is an ongoing global strategy; thus, this paper has relevance for all professionals involved in their care. Design: This is a discussion paper. Data Sources: This paper draws on the authors' research and is supported by literature and theory. Key terms and Boolean operators were used to identifiy English‐language papers published in January 1995 to January 2019 in nine databases and Google Scholar databases. Implications for nursing: Despite limited evidence specific to adolescent mothers, contextual studies suggest that social networking sites may enhance well‐being. Nurses and midwives need to understand adolescent mothers' use of online networks to aid development of innovative, health‐enhancing care strategies using adolescent‐familiar modalities. Conclusion: This paper highlights the need for further research regarding the value of professional engagement in online networks to enhance an adolescent's transition to motherhood. SUMMARY STATEMENT: What is already known about this topic? Social networking sites have demonstrated capacity to enhance social capital. Adolescent mothers use these platforms to seek information and support—to build social capital. Professionally moderated platforms may further enhance health outcomes for adolescent mothers. What this paper adds? The paper discusses the value/challenges of social networking site use for midwives and nurses. The paper discusses the potential for online, salutogenic, interdisciplinary approaches to care and highlights the need for further research into online applications to support adolescent mothers. The implications of this paper: The paper enables an enhanced understanding of the value of social networking sites to adolescent mothers. It discusses how midwives and nurses may move forward in terms of supporting adolescent mothers in online spaces. It makes suggestions as to how the nursing and midwifery professions may support practitioners to embed online modalities into care provision.